Chemokine induces phase transition from non-directional to directional migration during angiogenesis - Sako, Keisuke; Gui, Ning; Mochizuki, Naoki; Fukumoto, Moe; Nakajima, Hiroyuki (Cell Structure and Function, 2025)
During angiogenesis, sprouting endothelial cells (ECs) migrate and eventually connect to target vessels to form new vessel branches. However, it remains unclear how these sprouting vessels migrate toward the target vessels in three-dimensional space. We performed in vivo imaging of the cerebral capillary network formation in zebrafish to investigate how sprouting tip cells migrate toward their targets. Of note, we found that tip cells reach the target vessels through two phases: a non-directional phase and a directional phase. In the non-directional phase, sprouting tip cells dynamically extend and retract their protrusions at the leading front and have less directionality in their movement. In contrast, once tip cells enter the directional phase, they migrate directly toward the anastomotic targets. Chemokine receptor Cxcr4a and its ligand Cxcl12b are important for the phase transition to the directional phase. In cxcr4a mutants, sprouting tip cells lose their directionality and tend to connect to nearby sprouting ECs, resulting in altered capillary network patterning. Furthermore, in wild-type (WT) larvae, local Ca2+ oscillations were detected in protrusions of tip cells, specifically in the non-directional phase, but almost disappeared in the directional phase as a result of the Cxcr4-dependent phase transition. Thus, this study provides evidence of a chemokine-induced phase transition in migrating tip cells, which is important for proper vascular network formation in the zebrafish brain.Key words: angiogenesis, directional migration, live imaging, chemokine, Ca2+ dynamics, zebrafish